Exacerbation heterogeneity in COPD: subgroup analyses from the FLAME study - Vogelmeier,CF; Chapman,KR; Miravitlles,M; Roche,N; Vestbo,J; Thach,C; Banerji,D; Fogel,R; Patalano,F; Olsson,P; Kostikas,K; Wedzicha,JA (International Journal of Chronic Obstructive Pulmonary Disease, 2018)
Background: The FLAME study compared once-daily indacaterol/glycopyrronium (IND/GLY) 110/50 µg with twice-daily salmeterol/fluticasone (SFC) 50/500 µg in symptomatic patients with moderate to very severe COPD and a history of exacerbations in the previous year.Methods: This prespecified and post hoc subgroup analysis evaluated treatment efficacy on 1) moderate/severe exacerbations according to prior exacerbation history and treatment, and 2) types of exacerbations according to health care resource utilization (HCRU) during 1-year follow-up.Results: IND/GLY reduced the rate of moderate/severe exacerbations versus SFC in patients with a history of 1 exacerbation (rate ratio [RR]: 0.83, 95% CI: 0.75–0.93), ≥2 exacerbations (RR: 0.85, 95% CI: 0.70–1.03) and ≥2 exacerbations or ≥1 hospitalization in the previous year (RR: 0.86, 95% CI: 0.74–1.00). Prolonged time-to-first exacerbation was observed in all the groups according to exacerbation history. Moderate/severe exacerbations decreased with IND/GLY versus SFC, independent of previous treatment. IND/GLY significantly reduced rates of moderate/severe exacerbations treated with antibiotics (RR: 0.79, 95% CI: 0.67–0.93) and systemic corticosteroids and antibiotics (RR: 0.80, 95% CI: 0.70–0.91); rates of exacerbations treated with systemic corticosteroids alone were comparable (RR: 0.99, 95% CI: 0.80–1.22).Conclusion: Overall, IND/GLY demonstrated consistent beneficial effects versus SFC on moderate/severe exacerbations, independent of prior exacerbation history or treatment. The efficacy of IND/GLY on exacerbation prevention was superior to SFC for exacerbations treated with antibiotics with/without systemic corticosteroids and was similar for exacerbations treated with systemic corticosteroids alone.